Nutrient solutions for plant growth and fructan production in Vernonia herbacea - Cuzzuol, Geraldo Rogério Faustini; Carvalho, Maria Angela Machado; Zaidan, Lilian Beatriz Penteado; Furlani, Pedro Roberto (Pesquisa Agropecuaria Brasileira, 2005)
<!–[if gte mso 9]> Normal 0 <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR; p.MsoTitle, li.MsoTitle, div.MsoTitle margin:0cm; margin-bottom:.0001pt; text-align:center; mso-pagination:widow-orphan; font-size:10.0pt; font-family:Arial; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR; font-weight:bold; p.MsoBodyText, li.MsoBodyText, div.MsoBodyText margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; mso-bidi-font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> The limited growth of rhizophores of Vernonia herbacea in Hoagland solution demanded the definition of a nutrient solution for plants of V. herbacea, aiming at the increase of the rhizophore biomass and fructan production. This solution, named Vernonia, is comprised of Ca(NO3)2.4H2O 2.5 mmol L-1, KNO3 2.3 mmol L-1, KH2PO4 0.52 mmol L-1, Mg(NO3)2.6H2O 1.7 mmol L-1 and Na2SO4 1.3 mmol L-1. Its effect on plants was compared to that of Hoagland solution, both with different ionic strengths, 50%, 100% and 200%. The effect of the solutions on plant growth and fructan content was evaluated twice in a six-month period. Plants did not survive up to two months, when cultivated in 200% Hoagland solution. The 50% Vernonia solution was the most effective for rhizophore biomass increase and fructan production per plant. Growth of aerial organs was promoted in 100% Hoagland and Vernonia solutions. Compared to Hoagland, Vernonia solution contains less macronutrients, which confirms the hypothesis that plants adapted to the oligotrophic soils of the cerrado, as V. herbacea, demand less mineral nutrients to achieve full growth. <!–[if !supportEmptyParas]–> <!–[endif]–>